An Update on Calciphylaxis - García Lozano, José Alberto; Ocampo Candiani, Jorge; Martínez Cabriales, Sylvia Aideé; Garza Rodríguez, Verónica (Springer Nature, 2018)
Calciphylaxis, also known as calcific uremic arteriolopathy and uremic small artery disease with medial wall calcification and intimal hyperplasia, is a multifactorial cutaneous vascular disease characterized by chronic, painful, non-healing wounds that occur frequently in patients with chronic kidney disease, predominantly in those with end-stage renal disease. The pathogenesis remains unclear, and the development of calciphylaxis lesions depends on medial calcification, intimal fibrosis of arterioles and thrombotic occlusion. Despite an increase in reports of calciphylaxis in the literature and clinical recognition of demographic characteristics and risk factors associated with calciphylaxis, it remains a poorly understood disease with high morbidity and mortality. In this review, we analyze and summarize the clinical manifestations, pathogenesis and pathophysiology, histopathology, differential diagnosis, diagnostic workup and treatment modalities for calciphylaxis. Because of the lack of consensus regarding the optimal approach to and treatment of this disorder, a high degree of clinical suspicion, early diagnosis, and multimodal and multidisciplinary treatment in collaboration with dermatology, nephrology, wound care, nutrition and pain management specialties may improve survival in patients with calciphylaxis.